(untitled) (Journal of Pharmaceutical Negative Results, 2023)
A "high-risk infant" is a newborn who needs more attention and care than the average healthy term baby. Following up on high risk cases is crucial because it can help identify and intervene in those infants who need special care, such as those with prematurity, LBW, HIE, sepsis, pathological jaundice, hypoglycemia, etc. Materials and Methods: In this prospective study 222 newborns who had been delivered at Dr. D.Y Patil Medical College, Hospital, Pimpri, Pune were enrolled and those who came to follow up in well baby clinic and high risk OPD were assessed using HINE and DASII Results: HIE was present in 5.1% in term babies compared to 15.8% in preterm. Birth weight <1800gm was more common in preterm (84%) and in term, it was only 6.3%. Sepsis occurred in 26.3% in preterm and 3.2% in term babies. PPHN was diagnosed in 7.9% of preterm babies and 5.1% term babies. HMD was common in preterm (36.8%) compared to 4.4% in term babies. Among the babies with high-risk, 69 (72%) were in the borderline (71-90) and among normal babies,26 (26%) were in borderline mental DQ classification. Among the babies with high-risk, 73 (76%) were in the borderline (71-90) and among normal babies,44 (44%) were in borderline motor DQ classification. The proportion of babies in borderline was quite high in high-risk group when compared to normal and this was significant with the p value of <0.001. Among babies with high risk 36(37.5) had HINE of less than 70 at 6 months. There was a significant difference between the high-risk and normal group with a p value of <0.001. Conclusion: Developmental assessment must be carried out in conjunction with a medical assessment in high risk babies for appropriate additional testing and interventions.